Big-Five Personality Types of Students in Department of Primary School Teacher Education and the Effects on Self-Directed Learning - Ramadhani, Yulia Rizki; Jamna, Jamaris; Solfema, Solfema; Harputra, Yuswin; Harahap, Muhammad Syahril (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
This study aims to determine whether there is a personality influence of the Big Five Personality Traits model on self-directed learning in students of the PGSD study program - at Institut Pendidikan Tapanuli Selatan. The research used a quantitative approach, and the number of research participants was 190 active students in the PGSD study program-Institut Pendidikan Tapanuli Selatan using a voluntary sampling technique. Data collection uses a psychological scale to measure personality, namely the Big Five Personality Scale. And to measure self-directed learning using the self-rating Scale for Self-Directedness in Learning (SRSSDL) by Fisher Instruments. Data were analyzed using Structural Equation Modeling (SEM) and processed through SmartPLS3. The study results show a significant positive effect between the two big five personality dimensions, Extraversion and Openness to experience, on self-directed student learning. There was also an insignificant positive effect between the three big five personality dimensions, namely Agreeableness, Conscientiousness, and Neuroticism, on self-directed learning of students of the PGSD study program-Institut Pendidikan Tapanuli Selatan.